RELATIONSHIP BETWEEN HEALTH BEHAVIOR AND DENGUE HEMORRHAGIC FEVER (DHF) IN TUAN RONDAHAIM HOSPITAL, PAMATANG RAYA, 2016 - Riada Mareny (PT. Radja Intercontinental Publishing, 2020)
The number of cases of Dengue Hemorrhagic Fever (DHF) in Simalungun District based on health data sources from the Simalungun District Health Office in 2016 in Simalungun District reached 903 cases with 23 deaths. This research was conducted to determine the relationship between health behavior and the incidence of Dengue Hemorrhagic Fever (DHF) at Tuan Rondahaim Hospital Pamatang Raya in 2016. This type of research is descriptive with a population of 30 people and a sample of 30 people where the population is used as the sample. The results of this study obtained that the majority of respondents had negative data from Dengue Hemorrhagic Fever (DHF), namely 18 people (60Y6), the majority had a habit of cleaning water reservoirs, namely 17 people (56.7”0), the majority had a habit of closing water reservoirs, namely 16 people (53,390), the majority have a habit of not draining water reservoirs, namely 17 people (56.7″0), the majority have a habit of burying used water items, namely 16 people (53.3Y6), chi-sguare that the habit of cleaning, closing, draining, shelter water has a relationship with the incidence of Dengue Hemorrhagic Fever (DHF) because the p value is € 0.05. University of Efarina Pamatang Raya and using the results of this study will add knowledge and insight that will conduct further research on clean and healthy living behavior in all settings of life. The results of this study can be used as input for disease prevention and eradication program managers at Tuan Rondahaim Hospital Pamatang Raya in 2016, especially as a consideration in determining the strategy for preventing and eradicating Dengue Hemorrhagic Fever (DHF). Provide additional information and insight about the prevention and eradication of Dengue Hemorrhagic Fever (DHF). Future researchers can use the results of this study as basic data for further research on clean and healthy living behavior.